Eliminating the Low-Prevalence Effect in Visual Search With a Remarkably Simple Strategy. (May 2022) - Taylor, J. Eric T.; Hilchey, Matthew D.; Weidler, Blaire J.; Pratt, Jay
The low-prevalence effect in visual search occurs when rare targets are missed at a disproportionately high rate. This effect has enormous significance for health and public safety and has proven resistant to intervention. In three experiments ( N s = 41, 40, and 44 adults), we documented a dramatic reduction of the effect using a simple cognitive strategy requiring no training. Instead of asking participants to search for the presence or absence of a target, as is typically done in visual search tasks, we asked participants to engage in "similarity search"—to identify the display element most similar to a target on every trial, regardless of whether a target was present. When participants received normal search instructions, we observed strong low-prevalence effects. When participants used similarity search, we failed to detect the low-prevalence effect under identical visual conditions across three experiments.